STUDENTS’ PERSPECTIVE OF ENGLISH-INDONESIA TRANSLATION ON TWITTER WEB PAGES - Rima Rahmadhika Lindri (Universitas Jambi, 2023)
ABSTRACT This qualitative research was conducted by describing An Analysis of English-Indonesia Translation Quality on Twitter Web Pages. There was one question addressed. The question described how the quality of the Indonesian version of Twitter Web pages is. Method and the design applied in this research were descriptive qualitative. Population of this research is ten students of the seventh semester who have completed the translation practice course. To get the data for this research, the researcher has some steps; the first step to collect the data, the researcher gives the questionnaires to the participant. Then, the researcher sees how the results of the questionnaires. After that, the researcher can interview the participants according to the results of the questionnaires. It means there are two types of data collecting procedure: questionnaires and interviews. The results showed ten respondents admit that participants had good perceptions by selecting